When ethnic minorities divorce in multicultural Britain: a survey of legal challenges with a focus on the south asian experience - Belle, A (Gujarat National Law University, 2018)
This paper explores divorcing patterns among ethnic minorities in England – with a special focus on South Asians – and the challenges these minorities face when their customs interact with the secular and official law of England. Its argument is developed through three thematic sections. The first section, divided into three subsections, explores a few problems South Asian minorities face domestically – i.e. from their practices in England. In the second section, challenges from a conflict of laws perspective – i.e. where an overseas angle is involved – is detailed and evaluated. The third section, with the example of what is widely called the angrezi shariat, looks into the possibility and challenges of a parallel legal realm among ethnic minorities. The final part summarises and concludes. While the overarching focus of this analysis is on the English context, a subtler motivation behind this effort is rooted in the domestic context of South Asia, particularly in India. The growing call, among some sections of Indian society today, for a Uniform Civil Code is one which must be evaluated in light of the possible consequences it may invite. Though my analysis has been restricted to customs of divorce, it is hoped that it offers a sense of the challenges that would emerge when official and secular family laws attempt to prevail over its counterparts in the religious/personal realm. Needless to say, the success of a possible Uniform Civil Code in India will depend on the extent to which it addresses pitfalls faced by similar multicultural societies like England.